Eugenol inhibits non‐small cell lung cancer by repressing expression of NF‐κB‐regulated TRIM59. (1st April 2019) - Cui, Zhilei; Liu, Zhen; Zeng, Junxiang; Chen, Lei; Wu, Qiong; Mo, Jiahang; Zhang, Guorui; Song, Lin; Xu, Weiguo; Zhang, Shulin; Guo, Xuejun
Abstract : In view of the recognized anti‐tumor properties of eugenol against non‐small cell lung cancer (NSCLC) in cell culture, here we further set out to investigate the potential therapeutic effect of eugenol in vivo and elucidate the underlying molecular mechanism. The relative expression levels of TRIM59 and p65 in NSCLC were quantified by real‐time polymerase chain reaction. Xenograft tumor model was established with TRIM59‐deficient H1975 cells, and tumor progression was monitored. Kaplan–Meier's analysis was performed to measure overall survival. Protein levels of TRIM59 and p65 in xenograft tumor were determined by western blot. Direct binding of p65 on the TRIM59 promoter was analyzed by chromatin immunoprecipitation assay, and the regulatory effect was interrogated with luciferase reporter assay. Both TRIM59 and p65 were up‐regulated in NSCLC. Eugenol treatment significantly inhibited xenograft tumor progression and prolonged the overall survival of tumor‐bearing mice. Mechanistically, eugenol suppressed p65 expression, which subsequently decreased TRIM59 expression. TRIM59 deficiency fully recapitulated the anti‐tumoral phenotype elicited by eugenol. Ectopic expression of TRIM59 completely abolished the tumor suppressive effect of eugenol, which underlined the predominant role of TRIM59 in mediating the signaling downstream of eugenol treatment. Eugenol inhibited NSCLC via repression NF‐κB‐TRIM59 pathway.